Adolescents' Knowledge of Sexuality and Perceptions Regarding Teenage Pregnancy: A Qualitative Study among Secondary School Students in Ibadan, Southwest Nigeria - OreOluwa Scott-Ashley; Samson Akande; Ayodeji Adebayo; Oluwatomi Iken (Shiraz University of Medical Sciences, 2020)
Background: Adolescents are prone to myriads of developmental issues, including early sexual debut, risky sexual behaviours, sexually transmitted infections, teenage pregnancy and abortions. These challenges could be worse among adolescents who lack the understanding of sexuality. Mitigating these challenges among this age group, constituting two-thirds of the Nigerian population, may require exploring the knowledge and perceptions of sexuality and teenage pregnancy. Therefore, the present study aimed to investigate the knowledge of sexuality and perceptions about teenage pregnancy among in-school adolescents in Ibadan, Southwest Nigeria. Methods: We conducted a descriptive cross-sectional study using a qualitative approach. The population comprised 10-17-yearold female and male students of public and private secondary schools. We held focus group discussion sessions among 82 participants and manually analysed the data using a generated code book. Results: The mean age of participants was 13.5 years with a male to female ratio of 1.1:1; 51% of the subjects were from co-educational public schools. Participants' knowledge about the contextual meaning of sexuality was sub-optimal but better regarding the prevention of sexuality problems and the associated causes and problems. The participants perceived teenage pregnancy as being on the increase and replete with adverse consequences. The focus group discussants had divergent opinions as to what to do if involved in unwanted pregnancy. Conclusions: A knowledge gap existed with regards to sexuality among the study participants. It is advocated that interventions be conducted to review the current status of sexuality education in secondary schools.